Pengaruh Pendekatan Contextual Teaching And Learning Berbantuan Media Tiga Dimensi Terhadap Motivasi Dan Hasil Belajar Matematika - Elda Hidemi Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to analyze the effect of the three-dimensional media-assisted Contextual Teaching and Learning (CTL) approach on learning motivation and student learning outcomes of SDN 112233 Sidorejo. The research method used is a quasi-experimental method. The research hypothesis was tested by using two-way analysis of variance (ANOVA) with a significance level of 0.05. Furthermore, the homogeneity and normality test were carried out, then the two-way analysis of variance (ANOVA) test was carried out. Based on the calculation of the ANOVA test shows the value of Fcount (5.609)> Ftable (4.06) then H₀ is rejected Hₐ is accepted with the conclusion that the CTL learning approach is proven to have an effect on mathematics learning outcomes, based on the value of Fcount (33.630)> Ftable (4.06) then H₀ is rejected Hₐ is accepted with the conclusion that students who have learning motivation are proven to have an effect on student learning outcomes and the value of Fcount (1.020) <Ftable (4.06) then H₀ is accepted Hₐ is rejected and the significance value is 0.319> 0.05, with concluded that there is an interaction between CTL approach to student learning motivation and student learning outcomes.